Rationality, Spirituality, and Social Well-Being in the Thought of Ibnu Tufail - Sholihah , Mida Mar`atus; Hasan, Ahmadi; Umar, Masyithah; Khasyi`in, Nuril (Interdisciplinary Explorations in Research Journal, 2024)
Abstract This study examines the political thought of the Andalusian philosopher Ibn Tufail, whose seminal work Hayy ibn Yaqzan presents a philosophical discourse on the potential of human rationality in shaping societal welfare. Using a qualitative, hermeneutical approach, this research analyzes the conceptual framework underpinning Ibn Tufail’s perspectives on politics, economy, and spirituality. The findings suggest that Ibn Tufail’s political philosophy emphasizes the centrality of individual rational faculties in guiding human behavior, ethical conduct, and the organization of the polity. His narrative of Hayy, a self-taught man who develops a sophisticated understanding of the natural world and social dynamics through the power of reason alone, serves as a thought experiment to demonstrate the sufficiency of human intellect in attaining societal well-being. Furthermore, the study highlights Ibn Tufail's views on the management of scarce economic resources and the importance of aligning individual pursuits with the collective welfare. His ideas on the harmonious integration of material, intellectual, and spiritual realms provide a holistic framework for governing a just and prosperous society. The insights gleaned from this research contribute to a deeper understanding of the philosophical foundations of Ibn Tufail's political thought, which can inform contemporary discussions on the role of reason in addressing challenges in governance, social policy, and community development. The study also underscores the continued relevance of this Andalusian thinker's perspectives in the ongoing discourse on the relationship between the individual, the state, and the pursuit of the common good. Keywords: rationality, spirituality, social, ibnu Tufail Abstrak Penelitian ini mengkaji pemikiran politik filsuf Andalusia Ibnu Tufail, yang dalam karya monumentalnya Hayy ibn Yaqzan menyajikan wacana filosofis tentang potensi rasionalitas manusia dalam membentuk kesejahteraan masyarakat. Dengan menggunakan pendekatan kualitatif-hermeneutis, penelitian ini menganalisis kerangka konseptual yang mendasari perspektif Ibnu Tufail tentang politik, ekonomi, dan spiritualitas. Temuan menunjukkan bahwa filsafat politik Ibnu Tufail menekankan sentralitas fakultas rasional individu dalam membimbing perilaku manusia, etika, dan organisasi sistem politik. Narasi tentang Hayy, seorang manusia yang belajar sendiri dan mengembangkan pemahaman canggih tentang dunia alam dan dinamika sosial melalui kekuatan akal semata, berfungsi sebagai eksperimen pemikiran untuk mendemonstrasikan kecukupan intelek manusia dalam mencapai kesejahteraan masyarakat. Lebih lanjut, studi ini menyoroti pandangan Ibnu Tufail tentang pengelolaan sumber daya ekonomi yang langka dan pentingnya menyelaraskan tujuan individual dengan kesejahteraan kolektif. Ide-idenya tentang integrasi harmonis antara ranah material, intelektual, dan spiritual menyediakan kerangka holistik untuk memerintah masyarakat yang adil dan makmur. Wawasan yang diperoleh dari penelitian ini berkontribusi pada pemahaman yang lebih mendalam tentang landasan filosofis pemikiran politik Ibnu Tufail, yang dapat menginformasikan diskusi kontemporer tentang peran akal budi dalam mengatasi tantangan dalam tata kelola pemerintahan, kebijakan sosial, dan pembangunan masyarakat. Studi ini juga menekankan relevansi yang berkelanjutan dari perspektif pemikir Andalusia ini dalam wacana yang sedang berlangsung tentang hubungan antara individu, negara, dan pencapaian kebaikan bersama. Katakunci: rasionalitas, spiritualitas, sosial, ibnu Tufail